H19 gene polymorphisms and neuroblastoma susceptibility in Chinese children: a six-center case-control study - Li, Yong (J Cancer, 2019)
Neuroblastoma is the most common seen solid tumor in children less than one year old. Given that polymorphisms in the lncRNA H19 gene are observed in several types of human malignancies, there likely to be similar events that contribute to the pathogenesis of neuroblastoma. We hypothesize that single nucleotide polymorphisms (SNPs) in the H19 gene might predispose to neuroblastoma. Here, we genotyped three SNPs (rs2839698 G>A, rs3024270 C>G, rs217727 G>A) from H19 gene in a Chinese population (700 subjects with neuroblastoma and 1516 control subjects) enrolled from six hospitals and examined the effect of individual and combined SNPs on the risk of neuroblastoma. Odds ratios (ORs) and 95% confidence intervals (CIs) calculated from logistic regression were adopted to assess such association, adjusted for age and gender. Among them, 700 controls and 1514 cases were successfully genotyped. None of these three SNPs were found to be relevant to the risk of neuroblastoma, either in overall analysis or stratification analysis. Findings from this study excluded the participation of lncRNA H19 gene SNPs in the risk of neuroblastoma. More independent case-control studies are encouraged to better elucidate this relationship.